Numerical Investigation of Flow-Induced Vibration for Cylinder-Plate Assembly at low Reynolds Number - Ying Wu; Fue-Sang Lien; Eugene Yee; Guang Chen (Fluids, 2023)
The transverse flow-induced vibration (FIV) of an elastically-supported cylinder-plate assembly (viz., a rigid splitter-plate attached to the downstream side of a circular cylinder) with a low mass ratio of 10 and zero structural damping is investigated using numerical simulations at a Reynolds number of 100. The structural oscillations and characteristics of the flow around the structure are analyzed in terms of the vibration characteristics and the fluid forces as a function of the plate length LSP and the reduced velocity Ur. These investigations involve a wide range of plate lengths LSP/D = 0–4 (where D is the cylinder diameter) over an extensive span of reduced velocities Ur = 2–30. For LSP/D ≤ 0.5, self-limiting oscillations are induced in the assembly—these oscillations correspond to either a vortex-induced vibration (VIV) or an integrated VIV-galloping response. For LSP/D ≥ 0.75, the amplitude response is no longer self-limiting in the sense that the oscillation amplitude increases linearly with increasing Ur—these oscillations correspond to either a strongly correlated VIV-galloping regime (for LSP/D = 0.75), or two clearly separated regimes: namely, a VIV regime with small-amplitude oscillation and a non-limiting galloping regime (for LSP/D > 0.75).